2015
DOI: 10.1021/acsami.5b04083
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Transparent Nanohybrids with Heat Resistance Using High-Density Amorphous Formation and Uniform Dispersion of Nanodiamond

Abstract: A new technology for the production of transparent material using a "crystalline" polymer is proposed in the present study. Further, transparent and flexible crystalline polymer nanohybrid film containing well-dispersed nanodiamond filler was fabricated. Partially fluorinated crystalline polymer with switchboard-type lamellae results in high transparency as a consequence of the formation of a high-density amorphous structure based on high-temperature drawing just below the melting point at 110 °C. Although the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 65 publications
1
21
0
Order By: Relevance
“…As described above, in previous studies , it was found that when high‐temperature drawing carried out for crystalline fluorinated polymers with switchboard‐type lamellae (Fig. b), the amorphous region is densified, and refraction of the transmitted light at the crystalline/amorphous interface is suppressed.…”
Section: Resultssupporting
confidence: 51%
See 3 more Smart Citations
“…As described above, in previous studies , it was found that when high‐temperature drawing carried out for crystalline fluorinated polymers with switchboard‐type lamellae (Fig. b), the amorphous region is densified, and refraction of the transmitted light at the crystalline/amorphous interface is suppressed.…”
Section: Resultssupporting
confidence: 51%
“…Actually, neat P(VDF‐TeFE) has high transparency after five drawing cycles at 110°C (Fig. d) . Indeed, one of the targets of this study is the maintenance of transparency in the nanohybrids.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…The chemical modification and functionalization of diamond composite materials with different compounds or nanoparticles are frequently needed to make them appropriate for good dispersion or with suitable function in various applications. For examples, various organic molecules including redox active ferrocene moiety5, long-chain fluorinated polymer6, poly(epsilon-caprolactone) (PCL)7, triethylene glycol (EG) and azide (−N 3 ) groups8, can be used to modify diamond to obtain surface grafted diamond by various chemical reactions. Interestingly, the modification of diamond powder with fluorinated or aminated surfaces as well as special core-shell structures (diamond as core and TiN as shell) were beneficial to the next applications as electrocatalysts910.…”
mentioning
confidence: 99%